Scorpion - Attenborough, David; Aliband, David; Edwards, Tony (London : BBC Enterprises, 1979)
Among the first creatures on dry land, scorpions sre natural survivors, able to go for months without food and to withstand extremes of temperature which would kill most other creatures. The film looks into their private world at their complex and poignant mating dances, the terrifying way in which they capture prey and includes rare footage of the birth of baby scorpions
Backup available in VHS 1/2 in.
Keywords: Scorpions; Scorpions -- Behavior; Scorpions -- Venom